2017
DOI: 10.1371/journal.pone.0170882
|View full text |Cite
|
Sign up to set email alerts
|

Emergency obstetric care in a rural district of Burundi: What are the surgical needs?

Abstract: ObjectivesIn a rural district hospital in Burundi offering Emergency Obstetric care-(EmOC), we assessed the a) characteristics of women at risk of, or with an obstetric complication and their types b) the number and type of obstetric surgical procedures and anaesthesia performed c) human resource cadres who performed surgery and anaesthesia and d) hospital exit outcomes.MethodsA retrospective analysis of EmOC data (2011 and 2012).ResultsA total of 6084 women were referred for EmOC of whom 2534(42%) underwent a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…The recognition that the humanitarian sector is not immune from the need to demonstrate safe surgical care has led to calls for more robust outcome data and clearer accountability 7–9. Only few studies, limited by small study size and limited external validity, have addressed the composition of the surgical workforce employed by humanitarian organisations 10 11. Therefore, there is inadequate published data on whether different anaesthesia providers (eg, physician, nurse or other healthcare provider) are employed in different settings, and to what extent there is a physician expatriate presence within the team.…”
Section: Introductionmentioning
confidence: 99%
“…The recognition that the humanitarian sector is not immune from the need to demonstrate safe surgical care has led to calls for more robust outcome data and clearer accountability 7–9. Only few studies, limited by small study size and limited external validity, have addressed the composition of the surgical workforce employed by humanitarian organisations 10 11. Therefore, there is inadequate published data on whether different anaesthesia providers (eg, physician, nurse or other healthcare provider) are employed in different settings, and to what extent there is a physician expatriate presence within the team.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the umbilical cord winding causes the fetus to experience hypoxemia which resulting in fetal distress. Furthermore, fetal distress can inhibit the decline of fetal presentation to the lowest part of the fetus so that the risk of cesarean section is carried out (Yisma et al, 2013b, Kuppens, Smailbegovic, Houterman, De Leeuw, & Hasaart, 2017Wang, Kuromaki, Ochi, Kikugawa, Matsunaga, & Takagi, 2016;De Plecker et al, 2017;Markos & Bogale, 2016;Dalal & Purandare, 2018). WHO in 2003 reported that an estimation of the maternal mortality rate is around 289,000.…”
Section: Introductionmentioning
confidence: 99%